KESENIAN BALI DULU DAN KINI BARONG BANGKUNGâ - Anwar, Ahmad Khoirul (KEMADHA, 2012)
Culture and artÂ is alwaysÂ interestingÂ to be discussed especiallyÂ in this era of globalization . Culture itself is the essence of the life of the nation . One example is the Balinese culture is predominantly Hindu teachings are rooted in the Hindu religion . Balinese culture also has a clear identity that is expressive culture which includes the basic values ??ofÂ the dominantÂ . BaliÂ isÂ the appeal ofÂ the unique culture and populist. Various kinds of diversityÂ togetherÂ in creativity,Â taste andÂ intention. EveryÂ religionÂ hasÂ aÂ feastÂ dayÂ each,Â oneÂ of whichÂ isÂ theÂ feastÂ day ceremonies of Hindus in Bali is Galungan . Galungan is the victory of DharmaÂ (Â goodnessÂ )Â againstÂ adharmaÂ (evilÂ ).Â ImplementationÂ of GalunganÂ tinged with a series of unique and distinctÂ inÂ thisÂ feast enliven like PenjorÂ in pairsÂ inÂ front of each houseÂ ,Â the offerings are set high and in